Membrane having magnesium-lithium separation function and method for producing the same

CN117504623BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210908224.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2026-10-13
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

因此,如何高效地实现镁锂分离仍然面临很多挑战

Benefits of technology

[0010]本发明提供的膜,对镁离子的截留率高,在保证水通量没有明显降低的同时,还具有较高的镁锂分离效率,处理效率较高。本发明提供的膜,其拉伸强度和断伸长率等力学性能没有受到明显的影响,兼顾了锂吸附性能和膜的力学性能并且制备方法简单,具有广阔的产业化前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003773110210000151
    Figure BDA0003773110210000151
  • Figure BDA0003773110210000161
    Figure BDA0003773110210000161
  • Figure BDA0003773110210000171
    Figure BDA0003773110210000171
Patent Text Reader

Abstract

The application relates to the field of membranes, and discloses a membrane with magnesium-lithium separation function and a preparation method thereof. The method comprises the following steps: sequentially preparing a porous support layer, a polyamide layer and a modified layer on a substrate; wherein the modified layer is obtained by hydrogen bond complexation of tannic acid and an imidazole cation donor on the surface of the polyamide layer. The membrane has high magnesium-lithium separation efficiency and high treatment efficiency while ensuring that the water flux is not obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membranes, and more specifically to a membrane with magnesium-lithium separation function and its preparation method. Background Technology

[0002] In recent years, with the widespread application of new energy vehicles, the demand for lithium energy has gradually increased. In my country, the vast majority of lithium resources are found in salt lake brines. Besides lithium ions, salt lake water also contains large amounts of magnesium and sodium ions; therefore, extracting pure lithium resources from salt lakes presents significant technical challenges. Currently, membrane separation and adsorption methods are the most widely studied methods for lithium extraction from salt lakes.

[0003] However, existing commercial nanofiltration membranes are not designed for magnesium-lithium separation; their separation efficiency for magnesium and lithium ions is very low (magnesium-lithium separation coefficient less than 5), making them unsuitable for lithium extraction from salt lakes. Most research on membrane products for lithium extraction from salt lakes is still in the laboratory stage, and the magnesium-lithium separation coefficients of the prepared membranes remain below 20. Therefore, achieving efficient magnesium-lithium separation remains a significant challenge. Summary of the Invention

[0004] The purpose of this invention is to overcome the aforementioned problems in the prior art and provide a membrane with magnesium-lithium separation function and its preparation method. This membrane has high magnesium-lithium separation efficiency while ensuring that the water flux is not significantly reduced, resulting in high treatment efficiency.

[0005] To achieve the above objectives, the present invention provides a method for preparing a membrane with magnesium-lithium separation function, the method comprising: sequentially preparing a porous support layer, a polyamide layer and a modified layer on a substrate;

[0006] The modified layer is formed by hydrogen bonding of tannic acid and imidazole cationic donors on the surface of the polyamide layer.

[0007] Secondly, the present invention provides a membrane with magnesium-lithium separation function prepared by the method described above.

[0008] Thirdly, the present invention provides a membrane with magnesium-lithium separation function, the membrane comprising, in sequence, a substrate, a porous support layer, a polyamide layer and a modified layer;

[0009] The modified layer comprises a complex formed by hydrogen bonding of tannic acid and imidazole cationic donors, and at least some of the structural units provided by the tannic acid are also connected to the polyamide layer via ortho-positions of phenolic hydroxyl groups.

[0010] The membrane provided by this invention exhibits a high magnesium ion rejection rate, achieving high magnesium-lithium separation efficiency without significantly reducing water flux, resulting in high treatment efficiency. Furthermore, the membrane's tensile strength and elongation at break are not significantly affected, balancing lithium adsorption performance with membrane mechanical properties. Moreover, its preparation method is simple, demonstrating broad industrialization prospects. Detailed Implementation

[0011] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0012] In a first aspect, the present invention provides a method for preparing a membrane with magnesium-lithium separation function, the method comprising: sequentially preparing a porous support layer, a polyamide layer and a modified layer on a substrate;

[0013] The modified layer is formed by hydrogen bonding of tannic acid and imidazole cationic donors on the surface of the polyamide layer.

[0014] The inventors of this invention discovered in their research that the membrane prepared by the method described above has a high crosslinking density and positive charge density in the modified layer, which effectively retains divalent magnesium ions, making it difficult for magnesium ions in the liquid to pass through the separation membrane, while allowing monovalent lithium ions to pass through as much as possible, thereby achieving a high magnesium-lithium separation efficiency. The amino groups on the polyamide layer can effectively cooperate with the modified layer and also effectively retain magnesium ions. Under the combined effect of the above layers, the membrane also has a high water flux and a higher treatment efficiency.

[0015] It is understandable that the phenolic hydroxyl group and imidazole cation of tannic acid can form OH...N hydrogen bonds.

[0016] There are no particular restrictions on the substrate; it can be any material with sufficient supporting strength suitable for nanofiltration, reverse osmosis, etc. However, preferably, the thickness of the substrate is 30-150 μm, more preferably 50-120 μm.

[0017] According to the present invention, preferably, the average pore size of the substrate is 10-50 μm and the porosity is 30-85%.

[0018] According to the present invention, preferably, the material of the substrate is selected from at least one of polyester nonwoven fabric and polyethylene nonwoven fabric.

[0019] According to the present invention, a preferred method for preparing a porous support layer includes: coating a porous support layer material solution onto a substrate and immersing it in water at 10-30°C for 10-60 minutes. The specific coating method is not particularly limited; for example, a doctor blade can be used for coating.

[0020] According to the present invention, preferably, the coating conditions result in a porous support layer thickness of 10-100 μm, more preferably 30-60 μm. The thickness can be controlled by controlling the amount of coating applied.

[0021] According to the present invention, preferably, the concentration of the porous support layer material in the porous support layer material solution is 10-20 wt% (for example, it can be 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, and any value within the range formed by any two of the above values).

[0022] According to the present invention, preferably, the porous support layer material is selected from at least one of polyethersulfone, polysulfone, polyaryl ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryl etherketone.

[0023] According to the present invention, preferably, the number-average molecular weight of the porous support layer material is 50,000-100,000 g / mol.

[0024] According to the present invention, preferably, the solvent in the porous support layer material solution is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide. In the preparation, the porous support layer material is first dissolved in the solvent and degassed (degassed at 20-40°C for 60-180 min) to obtain the porous support layer material solution.

[0025] After coating, the material is immersed in water at 10-30℃ for 10-60 minutes. This allows the solvent of the porous support layer material solution to gradually leave the porous support layer. Through this phase transformation method, it is possible to further ensure that a support layer with a porous structure is obtained.

[0026] After the porous support layer is prepared, the material can be washed, such as by washing it 2-4 times.

[0027] According to the present invention, preferably, the method for preparing the polyamide layer includes: sequentially contacting the surface of the porous support layer with an aqueous phase containing polyamines and an organic phase containing polyacrylamide chlorides, and then performing heat treatment.

[0028] The method described above, which sequentially contacts an aqueous phase containing polyamines and an organic phase containing polyacrylamide chlorides, yields a polyamide layer through interfacial polymerization. This polyamide layer has a cross-linked structure and is dense and thin, further ensuring high magnesium-lithium separation efficiency and water flux. The contacting of the aqueous and organic phases can be carried out at room temperature, such as 23-28°C.

[0029] According to the present invention, preferably, the conditions for preparing the polyamide layer result in a polyamide layer thickness of 10-500 nm, more preferably 50-300 nm (for example, it can be 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 280 nm, 300 nm, or any value within the range formed by any two of the above values), and even more preferably 80-130 nm. According to the present invention, preferably, the contact time with the aqueous phase containing the polyamine is 5-100 s, more preferably 10-60 s.

[0030] According to the present invention, preferably, the contact time with the organic phase containing polyacryl chloride is 10-200 s, more preferably 20-120 s.

[0031] According to the present invention, preferably, the ratio of the concentration of polyamine in the aqueous phase containing polyamine to the concentration of polyacrylamide in the organic phase containing polyacrylamide is (0.1-10):1, more preferably (0.5-5):1.

[0032] According to the present invention, preferably, the concentration of the polyamine in the aqueous phase containing the polyamine is 0.1-10 wt%, more preferably 0.5-2.5 wt%.

[0033] According to the present invention, preferably, the concentration of polyacryl chloride in the organic phase containing polyacryl chloride is 0.01-1 wt%, more preferably 0.1-0.5 wt%.

[0034] The inventors of this invention have also discovered that satisfying the above ratio further ensures higher magnesium-lithium separation efficiency and water flux.

[0035] The organic solvent in the organic phase containing polyacrylamide chloride can be one or more of n-hexane, dodecane, n-heptane, and alkane solvent oil (which can be commercially available Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).

[0036] The volume of the aqueous phase containing polyamines and the volume of the organic phase containing polyacrylamide chlorides are not particularly limited, as long as the amount of polyamines in the aqueous phase or the amount of polyacrylamide chlorides in the organic phase can be guaranteed to form a suitable polyamide layer with a cross-linked structure on the membrane. Preferably, relative to 400 cm⁻¹, 2The membrane area, the total amount of polyamines in the aqueous phase can be 0.05-2g, and the total amount of polyacrylamide chlorides in the organic phase can be 0.0001-0.5g.

[0037] Under the conditions of the above concentration and contact time, the thickness of the polyamide layer can generally be 10-500 nm.

[0038] According to the present invention, preferably, the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine, and p-phenylenediamine, more preferably from at least one of polyethyleneimine, piperazine, and polyethylenepolyamine. The polyethyleneimine may be a branched polyethyleneimine with a weight-average molecular weight of 10,000-50,000 g / mol.

[0039] According to the present invention, preferably, the polyacrylamide chloride is selected from at least one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and phthaloyl chloride, more preferably trimesoyl chloride and / or terephthaloyl chloride. When there are multiple polyacrylamide chlorides, their specific types can be mixed in any proportion. For example, when the polyacrylamide chloride is trimesoyl chloride and terephthaloyl chloride, the weight ratio of trimesoyl chloride to terephthaloyl chloride can be 1:0.2-10.

[0040] To further ensure a dense polyamide release layer, preferably, the heat treatment temperature is 40-150°C, more preferably 50-120°C; the heat treatment time is 0.5-10 min, more preferably 1-5 min. A reaction occurs upon contact between the polyamine and the polyacrylamide chloride, but under the above conditions, the prepared polyamide release layer is denser.

[0041] According to the present invention, preferably, the method for preparing the modified layer includes: self-assembling tannic acid and an imidazole cationic donor on a polyamide layer; wherein the self-assembly method includes: contacting the polyamide layer with a tannic acid solution at 0.4-0.7 MPa, 10-30°C, and while the tannic acid solution remains flowing; and then contacting the polyamide layer with an imidazole cationic donor solution at 0.4-0.7 MPa, 10-30°C, and while the imidazole cationic donor solution remains flowing, thus completing one self-assembly. The above contact can be performed at room temperature (around 25°C).

[0042] The self-assembly reaction can be carried out in a cross-flow membrane tank. Water is pumped into the cross-flow membrane tank to maintain its flow and pressure, which can be controlled by a pressure regulating valve. Cross-flow membrane tanks are commonly used equipment, and the method of this invention can be performed in such equipment, resulting in a simple process that is easily industrialized. During the self-assembly reaction in the cross-flow membrane tank, for example, after tannic acid comes into contact with the material, the tannic acid solution is discharged, and the cross-flow membrane tank is repeatedly rinsed with deionized water to remove the tannic acid from the system.

[0043] In the cross-flow membrane pool, the pump continuously delivers solution to the pool. Therefore, the total amount of tannic acid or imidazole cation donors in the solution generally exceeds the amount that can be attached to the membrane surface for reaction, thus ensuring the acquisition of a modified layer with a suitable structure.

[0044] According to the present invention, preferably, the conditions for preparing the modified layer are such that the thickness of the modified layer is 5-200 nm, more preferably 10-50 nm.

[0045] Preferably, in a single self-assembly reaction, the contact time between the material and the tannic acid solution is 1-120 min, more preferably 10-60 min (for example, it can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, or any value within the range formed by any two of the above values).

[0046] Preferably, in a single self-assembly reaction, the contact time between the material and the imidazole cation donor solution is 1-120 min, more preferably 10-60 min (e.g., it can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, or any value within the range formed by any two of the above values).

[0047] Preferably, the ratio of the concentration of tannic acid in the tannic acid solution to the concentration of imidazole cation donor in the imidazole cation donor solution is 1:(8-12). Meeting this ratio further ensures more complete self-assembly.

[0048] Preferably, the concentration of tannic acid in the tannic acid solution is 0.00001-1 wt%, more preferably 0.001-0.1 wt%.

[0049] Preferably, the concentration of the imidazole cation donor in the solution is 0.0001-10 wt%, more preferably 0.01-1 wt%.

[0050] Preferably, the number of self-assembly reactions is 1-10 times, more preferably 2-5 times. It is understood that when the number of self-assembly reactions is greater than 1, the material that has completed one self-assembly reaction can simply repeat the above self-assembly steps. For example, when the number of self-assembly reactions is 2 times, the material that has completed one self-assembly reaction is brought into contact with tannic acid again under flowing conditions of 0.4-0.7 MPa, 10-30°C, and tannic acid solution; then, under flowing conditions of 0.4-0.7 MPa, 10-30°C, and imidazole cationic donor solution, the polyamide layer side of the material is brought into contact with imidazole cationic donor solution again to complete the second self-assembly reaction.

[0051] Within the above concentration and time range, modified layers with a thickness of 1-200 nm can generally be obtained.

[0052] According to the present invention, preferably, the imidazole cation donor is selected from at least one of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-butyl-3-vinylimidazolium bromide, 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-aminoethyl-3-methylimidazolium nitrate, and 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine. In particular, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine salt, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine salt, 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine salt, 1-aminoethyl-3-methylimidazolium nitrate and 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine salt can also form hydrogen bonds through oxygen and phenolic hydroxyl groups of tannic acid.

[0053] After preparation, the membrane can be immersed in deionized water for later use.

[0054] Secondly, the present invention provides a membrane with magnesium-lithium separation function prepared by the method described above.

[0055] Thirdly, the present invention provides a membrane with magnesium-lithium separation function, the membrane comprising, in sequence, a substrate, a porous support layer, a polyamide layer and a modified layer;

[0056] The modified layer comprises a complex formed by hydrogen bonding of tannic acid and imidazole cationic donors, and at least some of the structural units provided by the tannic acid are also connected to the polyamide layer via ortho-positions of phenolic hydroxyl groups.

[0057] According to the present invention, preferably, the thickness of the membrane is 40-260 μm, more preferably 80-190 μm.

[0058] Preferably, the thickness of the substrate is 30-150 μm, and more preferably 50-120 μm.

[0059] Preferably, the thickness of the porous support layer is 10-100 μm, and more preferably 30-60 μm.

[0060] Preferably, the thickness of the polyamide layer is 10-500 nm, and more preferably 80-130 nm.

[0061] Preferably, the thickness of the modified layer is 5-200 nm, and more preferably 10-50 nm.

[0062] Within the aforementioned thickness range, the four-layer structure can achieve better synergistic effects, further enabling the membrane to possess both a high magnesium-lithium separation coefficient and a high water flux.

[0063] The materials and parameters of the substrate, the materials and parameters of the porous support layer, the preparation method of the polyamide layer, and the specific selection of the imidazole cationic donor have been described previously and will not be repeated here.

[0064] According to the present invention, preferably, the Zeta potential of the modified layer is -10mV to 30mV, more preferably 3.5mV to 15mV. The modified layer has a large number of positively charged imidazole groups. The inventors have also discovered that when the above potential is met, the positive charge density on the membrane surface is higher, which allows for better retention of magnesium ions and better passage of lithium ions, thereby achieving higher magnesium-lithium separation efficiency. It is understood that the separation membrane can be measured using a Zeta potential analyzer, and the obtained potential value is the potential of the modified layer on the surface.

[0065] The preparation method of the modified layer has been described previously and will not be repeated here.

[0066] According to a preferred embodiment of the present invention, the water flux of the separation membrane is greater than or equal to 22 L·m -2 ·h -1 The MgCl2 desalination rate is greater than or equal to 98.9%; the magnesium-lithium separation coefficient is greater than or equal to 54.

[0067] Fourthly, the present invention also provides the application of the membrane with magnesium-lithium separation function as described in the second or third aspect in magnesium-lithium separation (especially lithium extraction from salt lakes).

[0068] According to a particularly preferred embodiment of the present invention, a membrane with magnesium-lithium separation function is prepared by the following method:

[0069] Polysulfone (number-average molecular weight of 80,000-90,000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 17-19% by weight. The solution was then degassed at 24-26°C for 100-130 min. Next, the polysulfone solution was coated onto a 70-80 μm thick polyester nonwoven fabric (as a substrate, with an average pore size of 10-20 μm and a porosity of 30-40%). The material was then immersed in water at 24-26°C for 50-60 min, allowing the polysulfone layer on the surface of the polyester nonwoven fabric to undergo phase transformation into a porous membrane. Finally, the material, including the porous support layer and the substrate, was washed 2-3 times with water.

[0070] The surface of the porous support layer (approximately 38-42 μm thick), comprising the substrate and the porous support layer, is contacted with an aqueous solution containing 0.5-0.55 wt% polyethyleneimine at 24-26 °C for 55-60 s, after which the solution is drained. Then, the upper surface of the support layer is contacted again with an Isopar E solution containing trimesoyl chloride and terephthaloyl chloride (the ratio of the concentration of polyamine in the aqueous phase containing polyamine to the concentration of polyacrylamide in the organic phase containing polyacrylamide is 5-6:1, and the ratio of the concentrations of trimesoyl chloride and terephthaloyl chloride is 1:3-5), at 24-26 °C for 55-60 s, after which the solution is drained. Finally, the membrane is placed in an oven and heated at 65-75 °C for 3-3.5 min.

[0071] The heat-treated product is loaded into a cross-flow membrane tank, with the polyamide layer side of the material in contact with the solution in the tank. The solution in the cross-flow membrane tank is a 0.001-0.005 wt% aqueous solution of tannic acid. After the cross-flow membrane tank is run at 0.6-0.65 MPa and 25-26℃ for 30-35 minutes, the solution is drained, and the cross-flow membrane tank is repeatedly rinsed with deionized water to remove the tannic acid from the system. 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl) is then added to the cross-flow membrane tank. An imine salt aqueous solution (the ratio of tannic acid concentration in the tannic acid solution to the imidazole cation donor concentration in the imidazole cation donor solution is 1:10.5-11.5) is prepared. After the cross-flow membrane cell is run at 0.6-0.65 MPa and 25-26℃ for 30-35 minutes, the solution is drained, and the cross-flow membrane cell is repeatedly rinsed with deionized water to remove residual 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide. The above operation is repeated to complete another self-assembly reaction to obtain the membrane.

[0072] The present invention will be described in detail below through embodiments.

[0073] In the following embodiments and comparative examples, water is circulated into the cross-flow membrane tank by a water pump, so that the water in the membrane tank is in a flowing state and has a certain pressure.

[0074] In the following examples and comparative examples, polyethyleneimine (weight average molecular weight of 25000 g / mol, branched polyethyleneimine), polyethylene polyamine, piperazine, pyromellitic tricarboxylic acid chloride, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine salt, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine salt, 1-butyl-3-vinylimidazolium bromide, etc., were all purchased from Bailingwei Technology Co., Ltd., and other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0075] Isopar E is a commercially available alkane solvent oil (purchased from Xilong Chemical).

[0076] In Examples 1-3, the method for preparing a porous support layer on a substrate includes:

[0077] Polysulfone (number-average molecular weight 80,000 g / mol, purchased from Bailingwei) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18% by weight. The solution was then degassed at 25°C for 120 min. Next, the polysulfone solution was coated onto a 75 μm thick polyester nonwoven fabric (as a substrate, with an average pore size of 10 μm and a porosity of 30%) using a doctor blade. The material was then immersed in water at 25°C for 60 min, allowing the polysulfone layer on the surface of the polyester nonwoven fabric to undergo phase transformation into a porous membrane. Finally, the material, containing the porous support layer and substrate, with an area of ​​400 cm², was washed three times with water. 2 .

[0078] Example 1

[0079] The surface of the porous support layer, which consists of a substrate and a porous support layer, was contacted with an aqueous solution (50 ml) containing 0.5 wt% polyethyleneimine at 25°C for 60 s, and then drained. Then, the upper surface of the support layer was contacted again with an Isopar E solution (30 ml) containing 0.02 wt% trimesoyl chloride and 0.08 wt% terephthaloyl chloride at 25°C for 60 s, and then drained. Finally, the membrane was placed in an oven and heated at 70°C for 3 min.

[0080] The heat-treated product was loaded into a cross-flow membrane tank, with the polyamide layer side of the material in contact with the solution in the tank. The solution in the cross-flow membrane tank was a 0.001 wt% aqueous solution of tannic acid. After the cross-flow membrane tank was run at 0.6 MPa and 25 °C for 30 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove the tannic acid from the system. Then, a 0.011 wt% aqueous solution of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt was added to the cross-flow membrane tank. After the tank was run at 0.6 MPa and 25 °C for 30 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove any residual 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt. This process was repeated to complete another self-assembly reaction, yielding the membrane.

[0081] Example 2

[0082] The surface of the porous support layer, which includes the substrate and the porous support layer, was contacted with an aqueous solution (50 ml) containing 2.1 wt% polyethylenepolyamine at 25°C for 40 s, and then drained. Then, the upper surface of the support layer was contacted again with an Isopar E solution (30 ml) containing 0.12 wt% trimesoyl chloride and 0.33 wt% terephthaloyl chloride at 25°C for 100 s, and then drained. Finally, the membrane was placed in an oven and heated at 120°C for 1 min.

[0083] The heat-treated product was loaded into a cross-flow membrane tank, with the polyamide layer side of the material in contact with the solution in the tank. The solution in the tank was a 0.01 wt% aqueous solution of tannic acid. After running the tank at 0.7 MPa and 30°C for 20 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove the tannic acid from the system. Then, a 0.09 wt% aqueous solution of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt was added to the tank. After running the tank at 0.7 MPa and 30°C for 20 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove any remaining 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt. This process was repeated to complete another self-assembly reaction, yielding the membrane.

[0084] Example 3

[0085] The surface of the porous support layer, which includes the substrate and the porous support layer, was contacted with an aqueous solution (50 ml) containing 1 wt% piperazine at 25°C for 15 seconds, and then drained. Then, the upper surface of the support layer was contacted again with an Isopar E solution (30 ml) containing 0.25 wt% trimesoyl chloride and 0.25 wt% terephthaloyl chloride at 25°C for 30 seconds, and then drained. Finally, the membrane was placed in an oven and heated at 60°C for 5 minutes.

[0086] The heat-treated product was loaded into a cross-flow membrane tank, with the polyamide layer side of the material in contact with the solution in the tank. The solution in the cross-flow membrane tank was a 0.1 wt% aqueous solution of tannic acid. After the cross-flow membrane tank was run at 0.4 MPa and 15 °C for 40 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove the tannic acid from the system. A 1 wt% aqueous solution of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt was added to the cross-flow membrane tank. After the cross-flow membrane tank was run at 0.4 MPa and 15 °C for 40 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove the residual 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt. The above operation was repeated to complete another self-assembly reaction to obtain the membrane.

[0087] Example 4

[0088] The membrane was prepared according to the method of Example 1, except that 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt was used instead of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0089] Example 5

[0090] The membrane was prepared according to the method of Example 1, except that 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt was used instead of 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0091] Example 6

[0092] The membrane was prepared according to the method of Example 1, except that 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt was replaced with 1-butyl-3-vinylimidazolium bromide.

[0093] Example 7

[0094] The membrane was prepared according to the method of Example 1, except that self-assembly was performed only once.

[0095] Example 8

[0096] The membrane was prepared according to the method of Example 1, except that the self-assembly was performed five times.

[0097] Example 9

[0098] The membrane was prepared according to the method of Example 1, except that the method for preparing the porous support layer on the substrate included:

[0099] Polysulfone (number-average molecular weight 50,000 g / mol) was dissolved in dimethyl sulfoxide to prepare a 10% by weight polysulfone solution, which was then degassed at 25°C for 120 min. The polysulfone solution was then coated onto a 120 μm thick polyethylene nonwoven fabric (as a substrate, with an average pore size of 50 μm and a porosity of 70%) using a doctor blade. The material was then immersed in water at 15°C for 60 min, allowing the polysulfone layer on the surface of the polyester nonwoven fabric to undergo phase transformation into a porous membrane. Finally, after three water washes, a material containing a porous support layer and a substrate with an area of ​​400 cm² was obtained. 2 .

[0100] Example 10

[0101] The membrane was prepared according to the method of Example 1, except that the method for preparing the porous support layer on the substrate included:

[0102] Polyacrylonitrile (number average molecular weight 100,000 g / mol, purchased from Bailingwei) was dissolved in N-methylpyrrolidone to prepare a 15% by weight polyacrylonitrile solution, which was then degassed at 25°C for 120 min. The polyacrylonitrile solution was then coated onto a 120 μm thick polyethylene nonwoven fabric (as a substrate, with an average pore size of 40 μm and a porosity of 40%) using a doctor blade. The material was then immersed in water at 30°C for 30 min, allowing the polyacrylonitrile layer on the surface of the polyethylene nonwoven fabric to undergo phase inversion into a porous membrane. Finally, after three water washes, a material containing a porous support layer and a substrate with an area of ​​400 cm² was obtained. 2 .

[0103] Example 11

[0104] The membrane was prepared according to the method of Example 1, except that the heat-treated product was not placed in a cross-flow membrane tank for self-assembly. Instead, at 25°C, the polyamide layer of the material was directly immersed in a beaker containing an aqueous solution of tannic acid (i.e., the pressure was not controlled and the solution was not flowing) for 30 minutes, after which it was removed and repeatedly rinsed with deionized water. At 25°C, the polyamide layer of the material was also directly immersed in an aqueous solution of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt for 30 minutes, after which it was removed and repeatedly rinsed with deionized water. This process was repeated to complete another self-assembly reaction, resulting in a separation membrane. In each self-assembly, the volume of the tannic acid solution (or imidazole cation donor) in the beaker was such that the total amount of tannic acid (or imidazole cation donor) exceeded the amount that could potentially adhere to the membrane and react.

[0105] Example 12

[0106] The separation membrane was prepared according to the method of Example 1, except that the concentration of tannic acid in the tannic acid aqueous solution was 0.0001 wt%, and the concentration of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in the 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt solution was 0.5 wt%.

[0107] Comparative Example 1

[0108] The membrane was prepared according to the method of Example 1, except that self-assembly was not performed, that is, the membrane was obtained directly after heat treatment.

[0109] Comparative Example 2

[0110] The membrane was prepared according to the method of Example 2, except that the heat-treated product was loaded into a cross-flow membrane tank, so that the polyamide layer side of the material was in contact with the solution in the cross-flow membrane tank. The solution in the cross-flow membrane tank was a 0.01 wt% tannic acid aqueous solution. After the cross-flow membrane tank was run at 0.7 MPa and 30°C for 20 min, the material was taken out to obtain the membrane (i.e., it was only in contact with the tannic acid aqueous solution once).

[0111] Comparative Example 3

[0112] The membrane was prepared according to the method of Example 1, except that polyethyleneimine was replaced with polyvinyl alcohol.

[0113] Test Example 1

[0114] The membranes prepared in the above examples and comparative examples were subjected to the following measurements:

[0115] The thicknesses of the membrane, porous support layer, and polyamide layer were measured using a micrometer and a scanning electron microscope. The thickness of the modified layer was obtained by subtracting the thicknesses of the substrate, porous support layer, and polyamide layer from the membrane thickness. The substrate thickness was the thickness measured before coating the porous support layer material solution.

[0116] The zeta potential of each membrane surface was measured using a zeta potential analyzer.

[0117] The results are shown in Table 1.

[0118] Table 1

[0119]

[0120] In Comparative Example 2, the thickness of the modified layer was due to the change in thickness caused by tannic acid; in Comparative Example 3, the thickness of the modified layer was due to the change in thickness caused by the reaction of tannic acid and polyvinyl alcohol.

[0121] Test Example 2

[0122] The separation membranes prepared in the above examples and comparative examples were subjected to the following measurements:

[0123] Water flux test:

[0124] The membrane was placed in a membrane tank, and the water permeation rate of the membrane was measured over 1 hour under conditions of 0.6 MPa and 25°C. The water flux was then calculated using the following formula:

[0125] J = Q / (A×t), where J is the water flux, Q is the water permeation rate (L), and A is the effective membrane area (m²). 2 ), where t is time (h).

[0126] Desalination rate and magnesium-lithium separation coefficient test:

[0127] The membrane was loaded into a cross-flow membrane tank containing a feed solution of 2000 ppm magnesium chloride and 100 ppm lithium chloride. After pre-compression at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.6 MPa. The concentrations of magnesium chloride and lithium chloride in the permeate were determined by ion chromatography, and the desalination rate was calculated using the following formula:

[0128] R = (C p -C f R is the desalination rate, C is the desalination rate, and C is the desalination rate. p C represents the concentration of magnesium chloride or lithium chloride in the original solution (measured by ion chromatography). f The concentration of magnesium chloride or lithium chloride in the permeate (measured by ion chromatography);

[0129] The lithium-magnesium separation coefficient is calculated using the following formula:

[0130] S=(C Li,p / C Mg,p ) / (C Li,f / C Mg,f )

[0131] Where S is the lithium-magnesium separation coefficient, C Li,p and C Li,f The concentrations of lithium ions in the permeate and feed solutions, respectively (measured by ion chromatography); C Mg,p and C Mg,f The concentrations of magnesium ions in the permeate and feed solution are respectively (measured by ion chromatography).

[0132] The results are shown in Table 2.

[0133] Table 2

[0134]

[0135]

[0136] As can be seen from Table 2, the embodiments using the technical solution of the present invention have both higher water flux and higher magnesium-lithium separation efficiency.

[0137] Furthermore, the tensile strength and elongation at break of the membranes prepared in each embodiment were measured by a tensile testing machine. It was found that their tensile strength and elongation at break were not significantly different from those of existing membranes used for magnesium-lithium separation. The membrane provided by the present invention not only has a high lithium adsorption capacity and a fast adsorption rate, but also its tensile strength and elongation at break performance are not affected, thus taking into account both lithium adsorption performance and membrane mechanical properties.

[0138] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing a membrane with magnesium-lithium separation function, characterized in that, The method includes: sequentially preparing a porous support layer, a polyamide layer, and a modified layer on a substrate; The modified layer is formed by hydrogen bonding of tannic acid and imidazole cationic donors on the surface of the polyamide layer; and at least some of the structural units provided by the tannic acid are also connected to the polyamide layer through the ortho position of the phenolic hydroxyl groups. The method for preparing the modified layer includes: self-assembling tannic acid and imidazole cationic donors on a polyamide layer; wherein the self-assembly method includes: contacting the polyamide layer with a tannic acid solution at 0.4-0.7 MPa, 10-30°C and while the tannic acid solution is kept flowing; and then contacting the polyamide layer with an imidazole cationic donor solution at 0.4-0.7 MPa, 10-30°C and while the imidazole cationic donor solution is kept flowing, thus completing one self-assembly. The imidazole cation donor is selected from at least one of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-butyl-3-vinylimidazolium bromide, 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-aminoethyl-3-methylimidazolium nitrate, and 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine.

2. The method according to claim 1, wherein, The thickness of the substrate is 30-150 μm; And / or, the average pore size of the substrate is 10-50 μm, and the porosity is 30-85%; And / or, the material of the substrate is selected from at least one of polyester nonwoven fabric and polyethylene nonwoven fabric.

3. The method according to claim 2, wherein, The thickness of the substrate is 50-120 μm.

4. The method according to claim 1, wherein, The method for preparing a porous support layer includes: coating a porous support layer material solution onto a substrate and immersing it in water at 10-30℃ for 10-60 minutes; And / or, the coating conditions result in a porous support layer thickness of 10-100 μm.

5. The method according to claim 4, wherein, The method for preparing the porous support layer includes: coating conditions that result in a porous support layer thickness of 30-60 μm; And / or, in the porous support layer material solution, the concentration of the porous support layer material is 10-20 wt%; And / or, the porous support layer material is selected from at least one of polyethersulfone, polysulfone, polyaryl ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryl etherketone; And / or, the number-average molecular weight of the porous support layer material is 50,000-100,000 g / mol; And / or, the solvent in the porous support layer material solution is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

6. The method according to claim 1, wherein, The method for preparing the polyamide layer includes: sequentially contacting the surface of the porous support layer with an aqueous phase containing polyamines and an organic phase containing polyacryl chlorides, followed by heat treatment; And / or, the conditions for preparing the polyamide layer result in a polyamide layer thickness of 10-500 nm.

7. The method according to claim 6, wherein, The method for preparing the polyamide layer includes: preparing the polyamide layer under conditions that result in a polyamide layer thickness of 50-300 nm; And / or, the contact time with the aqueous phase containing polyamines is 5-100 s; And / or, the contact time with the organic phase containing polyacryl chloride is 10-200 s; And / or, the ratio of the concentration of polyamine in the aqueous phase containing polyamine to the concentration of polyacryl chloride in the organic phase containing polyacryl chloride is (0.1-10):1; And / or, in the aqueous phase containing polyamines, the concentration of polyamines is 0.1-10 wt%; And / or, in the organic phase containing polyacryl chloride, the concentration of polyacryl chloride is 0.01-1 wt%.

8. The method according to claim 7, wherein, The contact time with the aqueous phase containing polyamines is 10-60 seconds; And / or, the contact time with the organic phase containing polyacryl chloride is 20-120 s; And / or, the ratio of the concentration of polyamines in the aqueous phase containing polyamines to the concentration of polyacrylamide chlorides in the organic phase containing polyacrylamide chlorides is (0.5-5):1; And / or, in the aqueous phase containing polyamines, the concentration of polyamines is 0.5-2.5 wt%; And / or, in the organic phase containing polyacryl chloride, the concentration of polyacryl chloride is 0.1-0.5 wt%.

9. The method according to claim 6, wherein, The polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine, and p-phenylenediamine; And / or, the polyacryl chloride is selected from at least one of pyromellitic chloroformyl chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride; And / or, the heat treatment temperature is 40-150℃; the heat treatment time is 0.5-10min.

10. The method according to claim 9, wherein, The polyamine is selected from at least one of polyethyleneimine, piperazine, and polyethylene polyamine; And / or, the polyacryl chloride is selected from trimesoyl chloride and / or terephthaloyl chloride; And / or, the heat treatment temperature is 50-120℃; the heat treatment time is 1-5 min.

11. The method according to claim 1, wherein, The conditions for preparing the modified layer allow for a thickness of 5-200 nm. And / or, in a single self-assembly reaction, the contact time between the polyamide layer and the tannic acid solution is 1-120 min; And / or, in a single self-assembly reaction, the contact time between the polyamide layer and the imidazole cationic donor solution is 1-120 min; And / or, the ratio of the concentration of tannic acid in the tannic acid solution to the concentration of imidazole cation donor in the imidazole cation donor solution is 1:(8-12). And / or, in the tannic acid solution, the concentration of tannic acid is 0.00001-1 wt%; And / or, in the imidazole cation donor solution, the concentration of the imidazole cation donor is 0.0001-10 wt%; And / or, the number of self-assembly reactions is 1-10.

12. The method according to claim 10, wherein, The conditions for preparing the modified layer resulted in a thickness of 10-50 nm. And / or, in a single self-assembly reaction, the contact time between the polyamide layer and the tannic acid solution is 10-60 min; And / or, in a single self-assembly reaction, the contact time between the polyamide layer and the imidazole cationic donor solution is 10-60 min; And / or, in the tannic acid solution, the concentration of tannic acid is 0.001-0.1 wt%; And / or, in the imidazole cation donor solution, the concentration of the imidazole cation donor is 0.01-1 wt%; And / or, the number of self-assembly reactions is 2-5 times.

13. A membrane with magnesium-lithium separation function, characterized in that, The membrane comprises, in sequence, a substrate, a porous support layer, a polyamide layer, and a modified layer; The modified layer comprises a complex formed by hydrogen bonding of tannic acid and imidazole cationic donors, and at least some of the structural units provided by the tannic acid are also connected to the polyamide layer via the ortho position of the phenolic hydroxyl groups. The modified layer is obtained by self-assembly of tannic acid and imidazole cationic donors on a polyamide layer; wherein the self-assembly method includes: contacting the polyamide layer with a tannic acid solution at 0.4-0.7 MPa, 10-30°C and while the tannic acid solution is kept flowing; and then contacting the polyamide layer with an imidazole cationic donor solution at 0.4-0.7 MPa, 10-30°C and while the imidazole cationic donor solution is kept flowing, thus completing one self-assembly. The imidazole cation donor is selected from at least one of 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-butyl-3-vinylimidazolium bromide, 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine, 1-aminoethyl-3-methylimidazolium nitrate, and 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine.

14. The membrane according to claim 13, wherein, The thickness of the membrane is 40-260 μm; And / or, the thickness of the substrate is 30-150 μm; And / or, the thickness of the porous support layer is 10-100 μm; And / or, the thickness of the polyamide layer is 10-500 nm; And / or, the thickness of the modified layer is 5-200 nm.

15. The membrane according to claim 14, wherein, The thickness of the membrane is 80-190 μm; And / or, the thickness of the substrate is 50-120 μm; And / or, the thickness of the porous support layer is 30-60 μm; And / or, the thickness of the polyamide layer is 80-130 nm; And / or, the thickness of the modified layer is 10-50 nm.

16. The membrane according to claim 13, wherein, The substrate has an average pore size of 10-50 μm and a porosity of 30-85%. And / or, the material of the substrate is selected from at least one of polyester nonwoven fabric and polyethylene nonwoven fabric; And / or, the porous support layer material is selected from at least one of polyethersulfone, polysulfone, polyaryl ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryl etherketone; And / or, the number-average molecular weight of the porous support layer material is 50,000-100,000 g / mol; And / or, the polyamide layer is synthesized from a polyamine and a polyacrylamide chloride, wherein the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine and p-phenylenediamine; And / or, the polyacryl chloride is selected from at least one of pyromellitic chloroformyl chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride.

17. The membrane according to claim 13, wherein, The polyamide layer is synthesized from a polyamine and a polyacryl chloride, wherein the polyamine is selected from at least one of polyethyleneimine, piperazine and polyethylene polyamine; And / or, the polyacryl chloride is selected from trimesoyl chloride and / or terephthaloyl chloride.

18. The membrane according to claim 13, wherein, The zeta potential of the modified layer is -10mV to 30mV.

19. The membrane according to claim 18, wherein, The zeta potential of the modified layer is 3.5 mV to 15 mV.

20. The membrane according to claim 13, wherein, In a single self-assembly reaction, the contact time between the polyamide layer and the tannic acid solution is 1-120 min; And / or, in a single self-assembly reaction, the contact time between the polyamide layer and the imidazole cationic donor solution is 1-120 min; And / or, the ratio of the concentration of tannic acid in the tannic acid solution to the concentration of imidazole cation donor in the imidazole cation donor solution is 1:(8-12). And / or, in the tannic acid solution, the concentration of tannic acid is 0.00001-1 wt%; And / or, in the imidazole cation donor solution, the concentration of the imidazole cation donor is 0.0001-10 wt%; And / or, the number of self-assembly reactions is 1-10.

21. The membrane according to claim 20, wherein, In a single self-assembly reaction, the contact time between the polyamide layer and the tannic acid solution is 10-60 min; And / or, in a single self-assembly reaction, the contact time between the polyamide layer and the imidazole cationic donor solution is 10-60 min; And / or, in the tannic acid solution, the concentration of tannic acid is 0.001-0.1 wt%; And / or, in the imidazole cation donor solution, the concentration of the imidazole cation donor is 0.01-1 wt%; And / or, the number of self-assembly reactions is 2-5 times.

Citation Information

Patent Citations

  • Nano-filtration membrane, preparation method and applications of thereof

    CN109692584A

  • Antibacterial and pollution-resistant reverse osmosis composite membrane and preparation method thereof

    CN112870990A